Shrub facilitative effects on the plant litter arthropod community shifts with decreasing precipitation in desertified ecosystems in northwestern China. (May 2022) - Zhang, Anning; Chang, Haitao; Liu, Rentao; Sternberg, Marcelo
Abstract: Understanding shrub effects on plant litter arthropod community structure in contrasting semiarid and arid grassland ecosystems could lead to the promotion of biodiversity conservation and sustainable management in afforested plantations. An investigation of litter arthropod abundance and diversity beneath the shrub canopy and in open spaces between shrubs was conducted via a litterbag field experiment during two consecutive years in a semiarid and an arid grassland ecosystem. Litter arthropod diversity and abundance were significantly higher in the shrub understory than in open spaces in the arid grassland. Furthermore, a similar abundance of both total mites and predatory mites was found in the shrub understory. However contrasting trends were found in the semiarid grassland. Significantly higher detritivorous mite abundance was found in the open areas between shrubs with no clear facilitation effects on the detritivore community. In conclusion, shrub facilitation could expand biodiversity conservation towards open spaces in extreme arid grasslands. The increasing drought expected for the region under climate change scenarios strengthens the importance of conserving shrub cover in these ecosystems to sustain biodiversity and ecosystem functioning. Highlights: Shrubs exerted facilitative effects on litter arthropod diversity. Shrub facilitation on biodiversity expanded into open spaces in extreme arid grasslands. Direct shrub effects or indirect precipitation effects via litter mass were on litter arthropod distribution.